The optimal postoperative analgesia method after total abdominal hysterectomy: Epidural patient-controlled analgesia or multimodal analgesia - (:unkn) unknown (My University, 2013)
Objective: The aim of our study was to compare the efficacy and side effects of patient-controlled epidural analgesia (PCEA) and multimodal analgesia after total abdominal liysterectomy (TAH). Method: Sixty patients, aged between 20-60 years, undergoing TAH were randomly assigned into two groups each containing 30 patients, as PCEA (Group E) and multimodal analgesia (Group M). In Group E, 15 ml %0.25 bupivakain HCl and 100 μg fentanil was administered through an epidural catheter placed at L3-4 in lateral decubitus position. In all patients, anesthesia was induced with 2 mg kg-1propofol and 0.5 mg kg-1atracurium iv and was maintained with 70%t30% N2O 1 O2 in 1 MAC sevoflurane. Anesthesia was induced by 2 MAC sevofluran and 70% N2O in O2 by controlled ventilation after endotracheal intubation. Preoperative heart rate, mean arterial pressure, peripheral oxygen saturation and end tidal CO2 levels vere recorded every 5 minutes. In Group E, 0.25% bupivacaine+100 μgfentanyl in 15 ml was injected epidurally from L3-L4 intervertebral space preoperatively and 0.25% bupivacaine+3μg ml-1 fentanyl solution was infused epidurally with a rate of 10 ml h-1peroperatively. In the recovery room, epidural patient-controlled analgesia (basal infusion 5 ml h-1, bolus 4 ml, lockout time 15 min) was started with 0.125% bupivacaine+3 μg ml -1fentanyl solution. In Group M, lorno.xicam 16 mg, dexamethasone 8 mg and paracetamol 1g iv were administered during induction and the surgeon infiltrated the incision with 20 ml of 0.25% bupivacaine at the end of the operation. At the recovery room, iv meperidine patient-controlled analgesia (10 mg ml-1) (1.5 ml bolus dose, 8 min lockout time) was started and paracetamol 1g three times a day and lornoxicam 16 mg twice a day iv were administered. Postopeatively, visual analogue scale (VAS) scores, additional analgesic requirement, side effects, gastrointestinal system (GIS) functions (time to first bowel sound, time to first defecation), mobilization time and discharge time were recorded. Results: There was no significant difference in mean arterial blood pressure, heart rate, VAS scores, additional analgesic requirement, side effects, time to first bowel sound, first mobilization and discharge lime between the groups (p<0.05). In Group E, time to first defecation was significantly earlier than those of Group M (p>0.05). Conclusion: In patients undergoing TAH, multimodal analgesia (iv meperidine PC A, lornoxicam, paracetamol, dexametasone and wound infiltration) provides equivalent analgesic effect and can be an alternative to epidural analgesia, although the time to first defecation was found to be earlier with epidural PCA.
Keywords: Multimodal analgesia; Patient controlled analgesia; Postoperative analgesia; Total abdominal hysterectomy